HANAFISM IN NORTH AFRICA UNTIL FIFTH CENTURY AH - Karadağ, Bekir (HITIT UNIV, 2019)
This study deals with the situation in North Africa until the fifth century AH of Hanafi School. In this context, information is given on how the Hanafi School spread in the region, important Hanafi jurisprudence (fakihs) and how it ended in the region. The Hanafite, that many judgeships and administrators are involved, spread with student activities and government support in North Africa. The Hanafite continued to exist in the region until the fifth century, came to an end due to many influences, such as political preferences, the mihne event, and the negative activities of Maliki jurisprudence (fakihs). This study is important because it examines the situation of the Hanafi school in North Africa which a different region in terms of fiqh history.
Keywords: Hanafi School; North Africa; Maliki School; Mihne Event; History of Islamic Law